Research on upgrading the informationization of college archives management based on information technology - Tang, Mingqi; Xin, Lei (Applied mathematics and nonlinear sciences, 2025)
Archives are an important part of information resources, a witness and record of history, and a reference basis for decision-making on future development. The article applies data mining technology to college archive information service, and conducts research on the upgrading of college archive management informationization. After the modular construction of university archive management information system, the blockchain-based digital archive traceability sharing scheme is proposed to realize the encryption processing of archive information. And the calculation formula of information gain rate in C4.5 algorithm is approximated and simplified to optimize the cumbersome calculation process of attribute selection in the tree building process. The C4.5 algorithm is applied to the university archive information service system to categorize the archive information. Applying the C4.5 algorithm to college records management, the degree of influence of each customer’s information on the frequency of visits is “identity”, “age”, “specialty”, “Gender”, and customers can be categorized into frequent and infrequent customers. In the transaction throughput analysis experiment of PAPBFT consensus algorithm, it is found that the throughput of traditional PBFT consensus algorithm gradually decreases with the increase of the number of nodes, and the consensus algorithm in this paper increases the throughput with the increase of the number of nodes N, which effectively mitigates the problem of the obvious decrease in throughput caused by the increasing number of nodes. This paper efficiently and safely realizes the upgrading of university archive management informationization.